2019
DOI: 10.12659/msm.916329
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Dexmedetomidine on Renal Dysfunction and Hemodynamic Stability in Malignant Obstructive Jaundice Patients During Peri-Operative Period

Abstract: Departmental sources Background: This study aimed to investigate effects of intra-operative administration with dexmedetomidine (Dex) on hemodynamics and renal function in patients with malignant obstructive jaundice. Material/Methods: Our randomized, double-blinded, placebo-controlled study was conducted among 40 patients with malignant obstructive jaundice between August 2009 and March 2011 in The Affiliated Hospital of Inner Mongolia Medical University. The 40 patients were randomly divided into 2 groups: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In clinical practice, the intraoperative use of dexmedetomidine was mainly used to assist in sedation, maintaining hemodynamic stability and preventing the patient's postoperative delirium. 22,[36][37][38] However, there was currently a lack of clinical evidence for the intraoperative use of dexmedetomidine in the nine types of non-cardiac major surgery to affect postoperative sleep disturbance. Clinicians seemed to have not noticed and considered this problem in their actual work.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the intraoperative use of dexmedetomidine was mainly used to assist in sedation, maintaining hemodynamic stability and preventing the patient's postoperative delirium. 22,[36][37][38] However, there was currently a lack of clinical evidence for the intraoperative use of dexmedetomidine in the nine types of non-cardiac major surgery to affect postoperative sleep disturbance. Clinicians seemed to have not noticed and considered this problem in their actual work.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several studies have compared the efficacy of dexmedetomidine at enhancing urine output and at decreasing the concentration of blood urea nitrogen and creatinine after surgery. [6][7][8] However, there is no general consensus about the target dose, timing of initiation and discontinuation of dexmedetomidine in this context. The primary objective of these meta-analyses was to characterize the use of dexmedetomidine and to evaluate its impact on renal markers and outcomes in patients after surgery.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…A total of 19 studies with 3,395 patients were included in the final pooled analyses. [3][4][5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23] Of these patients, 1,683 received dexmedetomidine while 1,652 did not. Study review and inclusion is outlined in Figure 1.…”
Section: Manuscript Identification and Characteristicsmentioning
confidence: 99%
“…Previous studies have suggested the beneficial effect of dexmedetomidine on hemodynamic stability. [ 27 , 28 ] Dexmedetomidine may induce biphasic hemodynamic alterations. Alpha-2 mediated vasoconstriction may result in transient tachycardia and elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%